2002
DOI: 10.1177/172460080201700202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Treatment on Serum PSA and Percent Free PSA Levels in Patients with Biochemical Criteria for Prostate Biopsy and Previous Lower Urinary Tract Infections

Abstract: Biochemical criteria for prostate biopsy may be modified in patients with a history of lower urinary tract infections due to variations greater than those explained by intraindividual biological variations, and may be influenced by the antibiotic treatment. These results suggest that subclinical inflammatory foci may influence PSA and %f-PSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 21 publications
1
27
1
Order By: Relevance
“…Scattoni et al, 16 compared the pathology results of prostatectomy with the preoperative f-PSA/t-PSA ratio and found a decreased ratio in the presence of histological signs of acute prostatitis. Lorente et al 17 found significant variations in t-PSA and f-PSA/ t-PSA ratios in patients with benign prostatic hyperplasia (BPH)-associated prostatitis and not in patients with BPH or cancer. On the contrary, Ornstein et al 18 did not find any change in f-PSA/t-PSA ratio in prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Scattoni et al, 16 compared the pathology results of prostatectomy with the preoperative f-PSA/t-PSA ratio and found a decreased ratio in the presence of histological signs of acute prostatitis. Lorente et al 17 found significant variations in t-PSA and f-PSA/ t-PSA ratios in patients with benign prostatic hyperplasia (BPH)-associated prostatitis and not in patients with BPH or cancer. On the contrary, Ornstein et al 18 did not find any change in f-PSA/t-PSA ratio in prostatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although these genes had been shown to be important in the development and metastasis of prostate cancer, it is not clear whether they can be used as biomarkers to predict the malignant tendencies and the outcome of the patients. The routinely used prostate cancer marker Prostate Specific Antigen (PSA) is a very useful tool to screen prostatic diseases, but it can be affected by many other factors 27 and moreover, it merely reflects the prostatic volume. Although it is a good indictor of the size changes in the prostate gland, PSA alone cannot accurately predict the nature of the prostate cells, nor distinguish between the benign and malignant status.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently back-calculated the CV b by subtracting CV a from CV t : CV b ϭ ͌ CV t 2 Ϫ CV a 2 (7 ). Fifteen studies reported considerable variability of serial tPSA concentrations, but it was impossible to derive the CV b because of sufficient information on CV t and CV a was lacking (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Biological Variation Estimatesmentioning
confidence: 99%